Research of influence ballistic characteristics of weapons on the shooting efficiency taking into account the safety of the small arm use - Bilenko, Alexander; Kyrychenko, Alexander; Kaidalov, Ruslan (Technology audit and production reserves, 2020)
The object of research is the process of performing a fire mission by employees of the security forces in the presence of unauthorized persons in the direction of fire. The paper investigates the influence of the ballistic characteristics of weapons on the effectiveness of performing fire missions by security forces, taking into account the security of the use of weapons. The purpose of the use of weapons by security forces is usually the cessation of the offender or its detention. In this case, the deaths or injuries of a hostage or an unauthorized person as a result of the use of weapons should qualify as failure to fulfill the assigned fire mission. An analysis of the tactics of actions and features of the use of weapons by security forces indicates that the main reason for the danger of the use of small arms for unauthorized persons is the excessive distance of the bullet’s flight, at which it maintains lethal action. At the same time, with this the distance of the lethal action of a bullet is one of the factors that can be corrected. It depends on a combination of the ballistic characteristics of the weapon, namely the muzzle speed and the ballistic coefficient of the bullet. The analysis of known studies shows that the existing scientific and methodological apparatus for determining the effectiveness of firing does not allow to determine the effectiveness of the execution of the fire mission, taking into account the safety of the use of small arms due to the imperfection of the corresponding models. The model of the process of performing the fire mission has been improved by taking into account the influence of the ballistic characteristics of the weapon on the probability of hitting unauthorized persons, which makes it possible to assess the safety of the use of weapons. As a result of the study of the influence of ballistic characteristics of weapons on firing efficiency, taking into account the safety of the use of weapons, it was found that there is a need to minimize the difference between the aiming range of the weapon and the range at which the bullet maintains lethal action. Excessive energy of a bullet increases the likelihood of hitting an outsider due to an increase in the area of the danger zone of its destruction as a result of through penetration of the target. The probability of performing a fire mission with a limitation on the safety of using weapons is positively affected by increasing the stability of the muzzle speed of a bullet.